Prevalence of resting bradycardia, resting hypotension and orthostatic hypotension in chronic spinal cord injury patients - Ashta, Kuldeep Kumar; Kumar, Ravi (International Journal of Advances in Medicine, 2017)
Background: Spinal cord injury (SCI) is a devastating event which usually leads to the impairment of autonomic nervous system and also causes many acute and chronic complications. There are very few clinical tests to assess the proper functioning of the autonomic nervous system. So, it is hypothesized to access the presence of resting bradycardia, resting hypotension and orthostatic hypotension and to use them as indirect indicators for the autonomic dysfunction in chronic spine cord injury (SCI) patients. Methods: The study was an analytic cross-sectional study, to assess the prevalence of resting bradycardia, resting hypotension and orthostatic hypotension in the spinal cord injury patients. Results: This study was conducted on 87 SCI patients, out of which 58 were paraplegics (21 having complete spinal cord injury, 37 with incomplete spinal cord injury) and 29 tetraplegics (13 with complete spinal cord injury, 16 with incomplete spinal cord injury). Orthostatic hypotension (67% vs 48.65%), resting hypotension (38.09% versus 29.7%) and resting bradycardia (33.33% versus 27.03%) were more amongst paraplegics patients with complete spinal cord injury as compared to paraplegics with incomplete spinal cord injury patients. All tetraplegic patients with complete spinal cord injury had resting bradycardia. Orthostatic hypotension, resting hypotension was found to be greater in tetraplegic patients with complete spinal cord injury. Conclusions: Complications due to autonomic impairment pose day to day difficulties in life of chronic SCI patients hampering their quality of life. So, the assessment of autonomic functions must be a part of clinical evaluation of individuals with SCI and efforts must be made to tackle these complications in the best possible way.